PATIENT PERCEPTIONS AND ADVOCACY IN ICHTHYOSIS: A REVIEW OF PSYCHOSOCIAL AND SUPPORTIVE CARE MODELS (Journal of Medical & Health Sciences Review, 2025)
Background:  Ichthyosis is a range of rare, genetically heterogeneous conditions that are skin disorders caused by over-scaling and hindrance in skin barrier. Clinical care has made a significant improvement however; patients experience very serious psychosocial, emotional and societal difficulties.   Objective: The objective of this review is to highlight the perception and the quality of life of the patients affected by ichthyosis experience and the role of advocacy and sponsorship organizations in championing patient-centered care.   Method: A comprehensive literature search was conducted across databases including PubMed, Scopus, and Google Scholar for articles published up to May 2024. Studies focusing on patient experiences, advocacy efforts, and care strategies in ichthyosis were included. Quality assessment was performed using the Critical Appraisal Skills Program (CASP) for qualitative studies and the Newcastle-Ottawa Scale (NOS) for observational studies.   Results: Thematic analysis revealed three findings: (1) high psychological and social load patients face because of visible symptoms, (2) emotional distress and social isolation, and (3) stratification points in communication between patients and healthcare providers. Advocacy organizations like the Foundation for Ichthyosis & Related Skin Types (FIRST) were identified as instrumental in education, psychosocial support, as well as policy advocacy.   Conclusion: Ichthyosis management should not only be limited to clinical outcomes but should also focus on emotional and social wellbeing of the patient. The networks of sponsorship and advocacy play a crucial role in closing the care gaps and enabling patients.